Cultural and Civilisational Links between India and Southeast Asia Historical and Contemporary Dimensions (Springer Singapore, 2018)
The books presents the study undertaken by the ASEAN-India Centre (AIC) at Research and Information System for Developing Countries (RIS) on India's cultural links with Southeast Asia, with particular reference to historical and contemporary dimensions. The book traces ancient trade and maritime links, Chola Empire and Southeast Asia, religious exchanges (the Hindu, Buddhist and Islamic heritage), language, scripts and folklore, performing arts, painting and sculpture, architecture, role of the Indian Diaspora, contemporary cultural interaction, etc.